Electrical control of skyrmion density via skyrmion-stripe transformation - Ang, Calvin Ching Ian (2021)
A comprehensive understanding of numerous electrical current-induced magnetic texture transformations is necessary to ensure the reliability of skyrmionic devices during operation. Here, we present an experimental study of unipolar current-induced skyrmion-stripe transformation in a Pt/Co/Fe/Ir magnetic bilayer. High current density pulses induce a densely packed skyrmion state, as commonly reported in many other studies, and skyrmion nucleation is expected to lessen with diminishing current density. However, at a lower current density where pinning effects become significant, a regime where current-induced skyrmion annihilation and skyrmion-to-stripe transformation is observed. Kerr imaging reveals that, under a low current pulse, the rapidly expanding stripes crowd out and annihilate the skyrmions before quickly decaying and leaving behind a sparse skyrmion population. Our findings establish an additional requirement of a minimum operating current density in the design of skyrmionic devices to avoid unintended skyrmion deletion. On the other hand, this skyrmion annihilation can also be strategically employed as a technique for skyrmion density control using solely current modulation in future skyrmionic devices.